15 years of the Iberoamerican Network of Toxicology and Chemical Safety - de la Peña, E.; Herrero, Ó. (Spanish Journal of Environmental Mutagenesis and Genomics, 2021)
Through a joint initiative of collaboration, between Dr. Barros, the Brazilian Society of Toxicology and the University of Sau Paulo, member of IUTOX, and Dr. de la Peña, then president of the Spanish Association of Toxicology (AETOX) and member the Spanish Research Council (CSIC); In that year, 2006, the activity of the Iberoamerican Network of Toxicology and Chemical Safety (RITSQ) began. The promoter meeting was held at the ALATOX congress in Santiago de Chile, we initially used its institutional infrastructure and later we carried out the aforementioned activity from a new domain (ritsq.org). We carry out the activities of the RITSQ through the following actions: 1st By publishing on the RITSQ website, the information on how many meetings of toxicological interest and chemical safety are organized, in Latin America, and in Portugal and Spain, the website is publishes in Portuguese and Spanish simultaneously; 2nd By presenting ad hoc posters in the different congresses, meetings and conferences, since 2007, 113 posters have been presented, all of them published on the website (ritsq.org); and 3rd Accounting the number of users 70,922, the number of sessions 103,016 and the number of page visits. 208,815. Since the creation of the RITSQ, a large number of activities have been carried out, including: news, congresses, courses, topics related to the RITSQ, dissemination, and toxicological and chemical safety dissemination. This opportunity is used to include information on voluntary organ donation, transplants save lives, 1 donation saves 8 lives, so I request, please, become Donors.